Singularity Sphere in The Heart of a Black Hole - Sadiq, Sabir (Transactions on Engineering and Computing Sciences, 2024)
In the present work, radius, density of a black hole singularity and escape velocity of an object from an external surface of singularity sphere will be determined by using original mathematical equations to solve the mystery of a singularity. The singularity is white and smooth ball of steeply compressed particular type of matter and energy in the point same as the size of atom or subatomic particles. The Singularity is a big mystery and illusion in the history of Astronomy and black hole’s theory. Scientist believed that the singularity has zero radius and infinity density when mass divided to the size of singularity by using density law. In fact, everything in the Universe has its limit radius, size, and density according to genuine equations of Physics. The radius of an event horizon, or black hole radius that named Schwarzschild radius can be calculated, but escape velocity from an external surface of a black hole is constant equal to the speed of light travel in the vacuum. The radius, density, spinning speed, angular momentum of a singularity ball, and escape velocity from external surface of a black hole’s singularity is changeable according to dynamic of a singularity creation and an environment of the formation of a singularity. Singularity is denser than any well-known celestial object, and denser than any type of matter that contained in structure of a black hole.